2022
DOI: 10.1038/s41467-022-28649-2
|View full text |Cite|
|
Sign up to set email alerts
|

Controlling process instability for defect lean metal additive manufacturing

Abstract: The process instabilities intrinsic to the localized laser-powder bed interaction cause the formation of various defects in laser powder bed fusion (LPBF) additive manufacturing process. Particularly, the stochastic formation of large spatters leads to unpredictable defects in the as-printed parts. Here we report the elimination of large spatters through controlling laser-powder bed interaction instabilities by using nanoparticles. The elimination of large spatters results in 3D printing of defect lean sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Therefore, the spattering needs to be solved during the in situ alloying process because it can lead to the deterioration of tensile performance by causing fusion defects. [ 43 ] The effective methods to eliminate the spattering include adjusting the parameter of shielding gas flow for removing the spatter from the printing zone and applying nanoparticle control on the instability of melting pool to eliminate large spatters, [ 44,45 ] which will be investigated in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the spattering needs to be solved during the in situ alloying process because it can lead to the deterioration of tensile performance by causing fusion defects. [ 43 ] The effective methods to eliminate the spattering include adjusting the parameter of shielding gas flow for removing the spatter from the printing zone and applying nanoparticle control on the instability of melting pool to eliminate large spatters, [ 44,45 ] which will be investigated in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Also wet coating of Al7075 (Vieth et al, 2020) and AlSi10Mg (Wang and Shi, 2020) with TiC nanoparticles by means of ultrasonication and wet ball milling was shown to be a feasible functionalization approach, although this process route has the drawback to demand for an additional drying step and potential contamination or oxidation of the alloy. Also for parts manufactured from Al6061/TiC composite powder prepared by planetary ball milling, a reduction of cracks was observed (Qu et al, 2022). Moreover, the authors observed improved PBF-LB/M processability characterized by a more stable process and the elimination of large spatters, which may lead to defective parts, for the composite powder system.…”
Section: Aluminum Alloy Feedstock Powdersmentioning
confidence: 92%
“…Currently, state-ofthe-art experimental characterization of the melting process uses high-speed imaging to capture the melting process and its dynamic interaction with the powder bed, such as powder spattering and denudation induced by the vapor plume [43] . Importantly, the use of in-situ operando X-ray synchrotrons has revealed many crucial information, such as the keyhole dynamics, its instability and pore formation [69] , and effects of nanoparticle additions [159] . Moreover, the combination of Schlieren imaging and in-situ x-ray operando imaging provides a simultaneous observation of the AM process and reveals the interaction between the vapor plume and melting process [70] .…”
Section: Mechanistic Modellingmentioning
confidence: 99%